2019
DOI: 10.1155/2019/5952435
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Osteonecrosis of the Tarsal Navicular: A Report of Two Cases

Abstract: Spontaneous osteonecrosis of the tarsal navicular, called the Mueller-Weiss syndrome, is an uncommon disease. Patients who are resistant to conservative treatment require operative treatment. However, there is no established operative treatment. Two cases of spontaneous osteonecrosis of the tarsal navicular with double (talonavicular and naviculocuneiform joints) arthrodeses with different locking plates are presented. Removal of necrotic areas from the tarsal navicular and replacement with autologous bone gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Therefore, arthrodesis, which involves several procedures, including fusion of the joint, is currently the most suitable surgical treatment. [18]. For patients with bipartite navicular bone, there may be no suitable treatment other than arthrodesis of the medial column.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, arthrodesis, which involves several procedures, including fusion of the joint, is currently the most suitable surgical treatment. [18]. For patients with bipartite navicular bone, there may be no suitable treatment other than arthrodesis of the medial column.…”
Section: Discussionmentioning
confidence: 99%
“…Reade et al demonstrated that isolated talonavicular arthrodesis was performed for Müller-Weiss disease of a 25-year-old female, and fusion of the talonavicular joint was confirmed four months postoperatively [ 17 ]. Kitaura et al showed that talonavicular arthrodesis and talonavicular-cuneiform arthrodesis were performed in two cases of Müller-Weiss disease; talonavicular-cuneiform arthrodesis achieved bone union, but talonavicular arthrodesis resulted in nonunion [ 18 ]. For patients with bipartite navicular bone, there may be no suitable treatment other than arthrodesis of the medial column.…”
Section: Discussionmentioning
confidence: 99%